Comparison of efficiency between two artificial insemination methods using frozen-thawed semen in domestic cat (Felis catus) Artificial insemination in domestic cats - Silva Balbin Villaverde, Ana Izabel [UNESP]; Melo, Cely Marini; Martin, Ian; Ferreira, Tatiana Henriques [UNESP]; Papa, Frederico Ozanam [UNESP]; Taconeli, Cesar Augusto [UNESP]; Lopes, Maria Denise [UNESP] (Elsevier B.V., 2009)
The aim of this study was to compare the efficiency of the intravaginal (IVAI) vs. intrauterine artificial insemination (IUAI) using frozen-thawed sperm in the domestic cat. Semen was collected from two tom cats using an artificial vagina and samples were assessed for motility (computer-assisted sperm analysis (CASA)), sperm morphology and plasma membrane integrity. After dilution with TRIS/OEP/YOLK (4% of glycerol), sperm samples were loaded into 0.25 mL straws (25 x 106 motile sperm/straw), incubated at 5 degrees C for 20 min and cryopreserved over liquid nitrogen (LNZ) vapor for 15 min and then immersed in LN(2). For each AI, four straws from the same male were thawed (12 s at 46 degrees C) and centrifuged at 250 x g for 8 min to pellet the sperm. The supernatant was discarded and sperm pellet resuspended with the remaining liquid, approximately 100 mu L, and analyzed as described above. Queens were treated with a single im injection of 100 IU eCG to induce ovarian follicular development. Final oocyte maturation and ovulation was induced with 100 IU hCG given im at 82-84 h after eCG administration. Thirty hours after hCG administration, females were inseminated either intrauterine (n=8 queens) or intravaginally (n=8 queens), using thawed sperm from a single male. Although a pronounced decrease in sperm motility, acrosome and plasma membrane integrity was observed in sperm samples from both cats, a pregnancy rate of 75% was achieved when using the intrauterine AI method compared with 0% pregnancy when inseminated intravaginally.
Keywords: Domestic cat; Artificial insemination; Frozen-thawed semen; Estrus induction; Ovulation induction